METHOD AND APPARATUS FOR PERFORMING COMPRESSION ON COLOR IMAGE - ROUSSEAU, NAOMI; BAREA ALAN; BURNOT CHRISTOPHE; BUSSCHAERT, CHARLES; ROUVROY GAEL; PELLEGRIN PASCAL (2024)
The present invention relates to a method of compressing a color image into a packed data set, the color image comprising color image samples arranged in a sampling pattern in a reference grid, and which comprises the steps of: (a) performing a decorrelation transformation, thereby providing a component image; (b) performing discrete wavelet decomposition on the component image for multiple times; and (c) forming packets in the packed dataset by processing each consecutive row and each component in the reference grid and grouping all samples of the component in the row in one or more packets, and appending the one or more packets to the packed dataset. The invention also relates to an apparatus for compression, a computer program for compression, a method for decompression, an apparatus for decompression and a computer program for decompression. The invention also relates to a packed data set generated by the method for compression. 本发明涉及一种将彩色图像压缩到打包数据集中的方法，该彩色图像包括按照采样模式布置在参考网格中的彩色图像样本，并且，其包括以下步骤：(a)执行去相关变换，从